Philosophical and Cultural Aspects of Transhumanism and Posthumanism - Roman Sapenko; Bogdan Trocha (International Society of Philosophy and Cosmology, 2020)
The article discusses the mechanisms of improving the human organism presented in past centuries' culture and analogous phenomena present in contemporary cultural texts. On this basis, theoretical and speculative aspects of posthumanism and transhumanism are described, their literary realizations, and finally, their cultural consequences are presented. Ideas, movements and ideologies, or even philosophies of posthumanism and transhumanism, although affecting the common problematic area, still cause confusion because of their mutual confusion with each other. The article tries to find arguments for the position that posthumanism and transhumanism stand in one house, but the latter is less suitable for understanding the radically changing world that we experience in such a painful way.